The Readers’ International: The Politics of Foreign Literature in War Times in Benjamin Fondane’s Essays - Adrian Tudurachi (RiCognizioni, 2014)
The Readers’ International. A foreign literature policy in war times in Fondane’s essays. Between 1919 and 1922, B. Fondane engaged himself into a legitimisation enterprise, which grew into a unique form of reading internationalism. By radically stating the subjective nature of all ‘preferences’, the essayist could figure out the character of a reader free from all national determinations, able to cross the cultural limits as well as the prejudices on their actual hierarchy. Our essay proposes to examine this form of contingence and contact with foreign literatures, inspired, paradoxically, by the warlike imaginary of the First World War.